IJABE SWAT Special Issue: Innovative modeling solutions for water resource problems - Gassman, Philip W.; Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2015)
The Soil and Water Assessment Tool (SWAT) ecohydrological model is used worldwide to evaluate hydrological and water quality concerns across a plethora of watershed scales and environmental conditions. The ten studies featured in this special issue confirm the global utility of SWAT, which include applications of the model in Brazil, China, Ethiopia and the United States. The range of applications reported in the special issue mirror broader trends in the extensive existing SWAT literature and provide valuable insights regarding input data sensitivity, testing, scenario analysis, software development and other important SWAT-related advancements. Brief summaries of these ten studies in this SWAT special issue are provided, highlighting key procedures and findings for each application. A brief description of SWAT structure and historical development is also given including a complete listing of key documentation and enhancements for every major release of the model between the early 1990s to the present time. This overview will serve as a guide to better reading and understanding of the ten research papers in this SWAT special issue of IJABE. Keywords: Soil and Water Assessment Tool (SWAT), SWAT special issue, modeling solutions, water resource, watershed DOI: 10.3965/j.ijabe.20150803.1763 Citation: Gassman P W, Wang Y K. IJABE SWAT Special Issue: Innovative modeling solutions for water resource problems. Int J Agric & Biol Eng, 2015; 8(3): 1－8